Odpowiedź:
7.
a)
3/5 * 0,1 - 10,8 = 0,6 * 0,1 - 10,08 = 0,06 - 10,08 = -10,02
b)
5 + (-3 1/6) * 0,6 = 5 - 19/6 * 3/5 = 5 - 19/2 * 1/5 = 5 - 19/10 = 5 - 1,9 = 3,1
c)
5,75 : (-1/4) + 25 = -5 3/4 * 4 + 25 = -23/4 * 4 + 25 = -23 + 25 = 2
d)
2 1/3 - 3,5 : 1 3/7 = 2 1/3 - 35/10 : 10/7 = 2 1/3 - 7/2 * 7/10 = 2 1/3 - 49/20 =
= 2 1/3 - 2 9/20 = 2 20/60 - 2 27/60 = -7/60
8.
a)
5 1/3 - 7,25 - 3/4 = 5 1/3 - 7 ,25 - 0,75 = 5 1/3 - 8 = -2 2/3
b)
1 5/6 - 1 1/12 - 0,5 : 2/3 = 1 10/12 - 1 1/12 - 1/2 * 3/2 = 9/12 - 3/4 = 3/4 - 3/4 = 0
c)
3² - 2³ * (-1/8) = 3² + 2³ * 1/2³ = 3² = 9
d)
(-4/5) : (0,2 * 2³ - 0,8) = -4/5 : (0,2 * 8 - 0,8) = -0,8 : (1,6 - 0,8) = -0,8 : 0,8 = -1
Szczegółowe wyjaśnienie: